2017
DOI: 10.1080/15592294.2017.1363952
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation-independent growth restriction and altered developmental programming in a mouse model of preconception male alcohol exposure

Abstract: The preconception environment is a significant modifier of dysgenesis and the development of environmentally-induced disease. To date, fetal alcohol spectrum disorders (FASDs) have been exclusively associated with maternal exposures, yet emerging evidence suggests male-inherited alterations in the developmental program of sperm may be relevant to the growth-restriction phenotypes of this condition. Using a mouse model of voluntary consumption, we find chronic preconception male ethanol exposure associates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 67 publications
(114 reference statements)
4
82
4
Order By: Relevance
“…In addition to these effects demonstrating vulnerability of the adult sperm methylome to alcohol, animals exposed to prenatal alcohol exhibited increased CpG methylation at the pro‐opiomelanocortin (POMC) gene promoter in sperm that is associated with reduced POMC expression and suppression of its HPA axis mediating function in offspring (Govorko et al., ). Not all results support methylation changes in response to ethanol, as one recent study found that paternal voluntary alcohol consumption, which altered cholesterol trafficking and hepatic fibrosis markers in offspring, had no effect on DNA methylation in sperm (Chang et al., ). In addition, despite a number of studies demonstrating effects of environmental perturbations on methylation in sperm, the effect sizes of significant changes in methylation at individual cytosines are often small (e.g., ~10 to 20%), and thereby, the significance for cross‐generational inheritance is hard to discern, given the high penetrance observed in many preclinical paternal epigenetic inheritance models (Shea et al., ).…”
Section: Effects Of Alcohol On Epigenetic Mechanisms In Spermmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition to these effects demonstrating vulnerability of the adult sperm methylome to alcohol, animals exposed to prenatal alcohol exhibited increased CpG methylation at the pro‐opiomelanocortin (POMC) gene promoter in sperm that is associated with reduced POMC expression and suppression of its HPA axis mediating function in offspring (Govorko et al., ). Not all results support methylation changes in response to ethanol, as one recent study found that paternal voluntary alcohol consumption, which altered cholesterol trafficking and hepatic fibrosis markers in offspring, had no effect on DNA methylation in sperm (Chang et al., ). In addition, despite a number of studies demonstrating effects of environmental perturbations on methylation in sperm, the effect sizes of significant changes in methylation at individual cytosines are often small (e.g., ~10 to 20%), and thereby, the significance for cross‐generational inheritance is hard to discern, given the high penetrance observed in many preclinical paternal epigenetic inheritance models (Shea et al., ).…”
Section: Effects Of Alcohol On Epigenetic Mechanisms In Spermmentioning
confidence: 94%
“…Thus, to test the hypotheses inspired by cross‐generational epidemiological data, preclinical investigators have utilized isogenic rodent strains under controlled laboratory conditions to directly test the effects of various paternal preconception exposures to a vast range of environmental insults on an equally expansive number of biological and behavioral measures in offspring. Most prominently featuring studies pertaining to dietary change, chronic stress, and various drugs of abuse, many paternal preconception exposures with rodents have now been found to directly impart complex physiological and behavioral phenotypes to offspring (for excellent reviews, see Rando and Simmons, , Chang et al., ; Goldberg and Gould, ). For instance, obese fathers confer deficits in glucose metabolism to offspring (Chen et al., ; Cropley et al., ; de Castro Barbosa et al., ; Fullston et al., ).…”
Section: Heritability Of the Preconception Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Bdnf methylation and mRNA changes in VTA associate with lower sensitivity to alcohol‐induced anxiolysis and lower alcohol consumption in male offspring (Finegersh and Homanics, 2014). However, a recent study in mice found no changes in sperm‐inherited DNA methylation in sires after voluntary alcohol consumption (Chang et al, 2017). Thus, in some instances, alcohol‐induced changes to the sperm epigenome can have long‐term functional consequences in male offspring.…”
Section: Alcoholmentioning
confidence: 99%
“…Paternal alcohol exposure induces several developmental aberrations. It reduces litter sizes (Emanuele et al, 2001a; Cicero et al, 1994a, b; Tanaka et al, 1982) and increases the number of runts (Bielawski et al, 2002; Meek et al, 2007; Bielawski and Abel, 1997; Abel, 1993; Chang et al, 2017), malformations (Mankes et al, 1982; Bielawski and Abel, 1997), and pup mortality (Cicero et al, 1994a, b; Meek et al, 2007) in rats and mice. Litters from alcohol‐exposed sires also exhibit increased (Emanuele et al, 2001b; Abel, 1995) or decreased male‐to‐female ratios (Abel, 1993).…”
Section: Alcoholmentioning
confidence: 99%